Evaluation of Drainage Channel Capacity on Rela–Sutomo Road, Medan City, Indonesia - Melvi Maulita Napitupulu; Ridho Azahar; Wisnu Prayogo; Fikryah Atikah Pane; Sarra Rahmadani; Rizky Simanjuntak; Ahmad Zulfikar (Journal of Infrastructure and Civil Engineering, 2026)
This study evaluated the capacity of the drainage system along Rela–Sutomo Road, Medan, to accommodate rainfall runoff and domestic wastewater. Rapid urban development and population growth have increased impervious surface coverage, surface runoff, and domestic wastewater generation, potentially exceeding the conveyance capacity of the existing drainage channels. This study aimed to determine whether the existing drainage system could accommodate the combined design discharge. The analysis included population projection using the least-squares method, estimation of domestic wastewater discharge, rainfall frequency analysis using the selected probability distribution for a 10-year return period, rainfall intensity estimation using the Mononobe method, runoff calculation using the rational method, and channel capacity calculation using Manning’s formula. Sediment depths and channel dimensions were directly measured across 10 drainage segments. The results showed that the design runoff discharge for the selected 10-year return period reached 24.46 m³/s, whereas the existing channel capacity was only 1.31 m³/s. Sediment accumulation reduced the effective cross-sectional area and decreased the channel capacity by up to 30%. Consequently, the combined inflow substantially exceeded the available channel capacity, indicating critical hydraulic overload and a high risk of flooding and surface inundation. The existing drainage system is therefore inadequate and requires channel normalization, periodic sediment removal, and hydraulic capacity improvement